Exploiting sensor redundancy for the calculation of fractional derivatives in the presence of noise - Machado, J. A. Tenreiro (2014)
In this paper a new method for the calculation of the fractional expressions in the presence of sensor redundancy and noise, is presented. An algorithm, taking advantage of the signal characteristics and the sensor redundancy, is tuned and optimized through genetic algorithms. The results demonstrate the good performance for different types of expressions and distinct levels of noise.